Impact of menstrual cycle on the diagnostic performance of LCR, TMA, and PCE for detection of Chlamydia trachomatis in home obtained and mailed vaginal flush and urine samples. Issue 4 (1st August 1999) - Møller, J K; Andersen, B; Olesen, F; Lignell, T; Ostergaard, L
Abstract : OBJECTIVES: To assess the impact of the menstrual cycle on the diagnostic performance of various assays for detection of Chlamydia trachomatis in home obtained and mailed vaginal flush and urine specimens. METHODS: A ligase chain reaction assay (LCR; Abbott Laboratories), a transcription mediated amplification assay (TMA; Gen-Probe), and an enzyme amplified immunoassay (PCE; Dako Diagnostics) were evaluated for their validity in detecting C trachomatis in vaginal flush, first void urine, and midstream urine specimens obtained by female high school students at home and mailed directly to the diagnostic laboratory. RESULTS: C trachomatis was detected in 45 of 889 females (5.1%). The vaginal flush material was positive by TMA and LCR in 84% and 82% of the chlamydia positive females, respectively. First void urine was positive by TMA in 73% and by LCR in 49% of the cases. Midstream urine was positive by TMA and LCR in 69% and 42% of the females, respectively. On a pool of first void and midstream urine, PCE detected 49% of the chlamydia positive females. The overall prevalence of C trachomatis increased with increasing time after the last menstrual bleeding. In urine samples, but not vaginal flush specimens, obtained 3 weeks after the last menstrual bleeding, the sensitivities of TMA, LCR, and PCE decreased markedly suggesting that inhibitors to the assays are excreted in the urine but not in vaginal secretions at this time. CONCLUSION: Vaginal flush samples are superior to urines for detection of chlamydia infections in females. In screening of young asymptomatic females, samples should be obtained in the latter part of the menstrual cycle.